Effectiveness Extract Temulawak (Curcuma zanthorrhiza) as an Insecticide Against Kutu Rambut (Pediculus humanus capitis) - Rosi Esa Gustina; Visna Septiandari (CV. Inara, 2026)
Temulawak (Curcuma zanthorrhiza) contains secondary metabolite compounds that allow this plant to be used as an alternative insecticide. Several secondary metabolite compounds of temulawak, namely phenols, terpenoids, flavonoids, saponins, alkaloids and tannins have insecticidal properties against head lice. This study aims to study the effectiveness of administering temulawak extract against kutu rambut (Pediculus humanus capitis). This study is experimental, namely in the form of administering temulawak extract to head lice. The extract used was divided into 4 concentrations, namely 0% (K0), 7% (P1), 9% (P2) and 11% (P3). The results of the One Way ANOVA analysis showed a significant difference in the average percentage of kutu rambut deaths between the control group and the treatment group with a value (p = 0.001 <α (0.05)). The Bonferroni post hoc test revealed a significant difference in the average percentage of kutu rambut deaths between group K0 and group P1 (p=0.028), between group P2 and group P3 (p=0.045), between group P1 and group P3 (p=0.002), and between group P2 and group P3 (p=0.048). However, there was no significant difference in the average percentage of kutu rambut deaths between group P1 and group P2 (p=0.185). This is considered effective as an insecticide against kutu rambut at concentrations of 9% and 11%, as the average percentage of kutu rambut deaths at the 9% concentration was 50-60%, and at the 11% concentration the average number of kutu rambut deaths was 80-90%.